Injectable Single-Component Peptide Depot: Autonomously Rechargeable Tumor Photosensitization for Repeated Photodynamic Therapy - Cho, Hong-Jun; Park, Sung-Jun; Jung, Woo Hyuk; Cho, Yuri; Ahn, Dong June; Lee, Yoon-Sik; Kim, Sehoon (AMER CHEMICAL SOC, 2020)
The general practice of photodynamic therapy (PDT) comprises repeated multiple sessions, where photosensitizers are repeatedly administered prior to each operation of light irradiation. To address potential problems arising from the total overdose of photosensitizer by such repeated injections, we here introduce an internalizing RGD peptide (iRGD) derivative (Ppa- iRGDC-BK01) that self-aggregates into an injectable single-component supramolecular depot. Ppa-iRGDC-BK01 is designed as an in situ self-implantable photosensitizer so that it forms a depot by itself upon injection, and its molecular functions (cancer cell internalization and photosensitization) are activated by sustained release, tumor targeting, and tumor-selective proteolytic/reductive cleavage of the iRGD segment. The experimental and theoretical studies revealed that when exposed to body temperature, Ppa-iRGDC-BK01 undergoes thermally accelerated self-assembly to form a supramolecular depot through the hydrophobic interaction of the Ppa pendants and the reorganization of the interpeptide hydrogen bonding. It turned out that the self-aggregation of Ppa-iRGDC-BK01 into a depot exerts a multiple-quenching effect on the photosensitivity to effectively prevent nonspecific phototoxicity and protect it from photobleaching outside the tumor, while enabling autonomous tumor rephotosensitization by long sustained release, tumor accumulation, and intratumoral activation over time. We demonstrate that depot formation through a single peritumoral injection and subsequent quintuple laser irradiations at intervals resulted in complete eradication of the tumor. During the repeated PDT, depot-implanted normal tissues around the tumor exhibited no phototoxic damage under laser exposure. Our approach of single-component photosensitizing supramolecular depot, combined with a strategy of tumor-targeted therapeutic activation, would be a safer and more precise operation of PDT through a nonconventional protocol composed of one-time photosensitizer injection and multiple laser irradiations.
Keywords: SPECTROSCOPY